Scientific Article Writing: Will ChatGPT Help? - I. M. Zashikhina (Moscow Polytechnic University, 2023)
The emergence of artificial intelligence language services has raised hopes related to facilitating the task of publication activity. Members of the academic community wondered whether chatbots could optimize the process of scientific writing. ChatGPT, a language model capable of, among other things, generating scholarly texts, received particular attention. The cases of writing academic papers using ChatGPT have led to a number of publications analyzing the pros and cons of using this neural network. In this paper, we investigate the possibility of using ChatGPT to write an introduction to a scientific paper on a topical issue of the Arctic governance. A set of queries to ChatGPT network, based on the logic of the commonly accepted in academia publication format IMRAD, has being developed. This format is characterized by structural and functional elements, which served as a logical basis for the queries. The responses received from ChatGPT were analyzed for their compliance with the requirements for a scientific article, according to the IMRAD publication format. The result of the analysis showed that ChatGPT is not able to meet the requirements for publishing a scientific article in the modern scientific publication discourse.